Multiple intelligences approach to infuse critical thinking skills among preschoolers / Yong Siew Nget - Yong , Siew Nget (2020)
Critical thinking skills (CTS) are regarded as the imperative skills for the complex and rapidly changing twenty-first century. The national educational goal should focus on developing CTS during early years. However, the infusion of CTS is not evident in our national preschool curriculum. There are no explicit guidelines and instructional consensus for teaching CTS in preschool. Thus, this study aimed to explore the ‘how’ and ‘what’ for the teaching and development of CTS among preschoolers through the adoption of the Multiple Intelligences approach (MIA). In addition, this study also explored how the acquired CTS can be applied for solving problems by selected preschoolers. An exploratory case study approach was conducted among a class of twenty preschoolers (six-years-old), in a private preschool which has been adopting MIA for the past fifteen years. This study began with a feasibility study to gauge the readiness of young children towards critical thinking. A set of instructional support materials (ISM) with fifteen CTS infused MI based lessons which hinged on the framework established by a panel of ECCE experts was then designed for teaching CTS in the selected preschool classroom. Data collection was done basically through qualitative methods involving some quantitative data. Class observations on the implementation of all the fifteen lessons were conducted and audio-video recorded by the researcher. Semi-structured interviews with selected teachers and principal and focus-group interviews with selected preschoolers were also conducted. The qualitative data collected were analysed using the constant comparative method for an in-depth description on the development of CTS among selected preschoolers. Two instruments, the Preschool Critical Thinking Skills Tests (PSCTST: Pre-Assessment and Post-Assessment) were developed for assessing the CTS levels of children before and after the implementation of ISM. The quantitative data collected from the tests were analysed using simple descriptive statistics for this exploratory case study. The score results of the Post-PSCTST revealed a notable improvement in the CTS levels of selected preschoolers after the ISM implementation. Thus, ISM implementation was found to have enhanced the teaching and development of CTS through multiple modalities of learning. From this study, six themes were identified as contributive factors towards the CTS development: readiness, explicit teaching, scaffolding, routines, classroom climate and interplay of MI strengths. Selected preschoolers with similar strengths were found to work and think together more effectively in the same MI groups. Through the process of problem-solving tasks, selected preschoolers were found to have applied CTS systematically in relation to the cognitive aspects of interpretation of problem, analysis of information provided, making inferences of solutions and evaluating their choices before presenting the solutions. The essence of this study showed that preschoolers can learn and apply CTS in various contexts of problem-solving regardless of their dominant MI strengths. Hence, it can be concluded that a conducive thinking challenging environment (with MIA as the vehicle in this present study) is the essential medium for teaching CTS explicitly. Several implications and suggestions were put forward to various stakeholders and researchers.